Age segmentation in the Chilean health system - Tokman, Marcelo (Estudios de Economía, 2016)
A formal model of the Chilean dual health system is presented, which, for appropriate parameters, replicates the observed age segmentation of the population between the private insurance market and the public health insurance. The model is used to compare the level of welfare obtained in the current mixed system with the levels of welfare that could be obtained in alternative “pure” systems, either only private or only public. It is also used to determine how the result of this comparison is affected by intergenerational distribution of income. Finally, the model is used to show that the creation of a mandatory individual savings account to finance the elderly’s health insurance could improve the performance of the Chilean health sector by reducing intergenerational inequality.